PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BARATA INDONESIA JAKARTA - Putri Huriah Agustina; Suroto (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of Work Motivation and Discipline on Employee Performance partially and simultaneously at PT Barata Indonesia. This research method uses quantitative analysis methods, namely using 70 respondents. Data analysis techniques in this research are using instrument tests, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, as well as hypotheses using the t test and f test. Regression equation Y = 14.598 + 0.258X1 + 0.436X2. The correlation coefficient value obtained was 0.753, meaning that the independent variable and the dependent variable had a very strong level of influence with a coefficient of determination or simultaneous influence of 55.5%, while the remaining 44.5% was influenced by variables not examined in this research. The partial hypothetical results of the motivation variable (X1) obtained a value of tcount > ttable (7.409 > 1.995), this was also strengthened by a significant value of 0.000 < 0.005. Thus motivation has a significant effect on employee performance. The work discipline variable (X2) obtained a value of tcount > ttable (8.647 > 1.995), this was also confirmed by a significant value of 0.000 < 0.005. Thus, work discipline has a significant effect on employee performance. Based on the results of the simultaneous analysis, the value Fcount > Ftable or (43.958 > 3.130) is obtained. This is also reinforced by the probability significance of 0.000 < 0.05. Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between Work Motivation and Work Discipline on employee performance at PT Barata Indonesia.